Healthcare Management in India: Issues, Challenges and Prospects - Pushpa Hongal; Yashpal Kshirsagar. IFS. (International Journal of Engineering and Management Research, 2023)
Healthcare management in India faces numerous challenges due to the country's size, population, and socio-economic diversity. The issues include inadequate funding, insufficient infrastructure, scarcity of healthcare professionals, and high out-of-pocket expenses, among others. These challenges have a significant impact on healthcare accessibility, quality, and affordability. Despite the challenges, healthcare management in India presents several prospects. For instance, the government is increasing healthcare spending, introducing new policies, and promoting public-private partnerships to address the challenges. Additionally, there is growing interest in telemedicine, digital health, and medical tourism, which can enhance healthcare accessibility and affordability. Healthcare management in India faces significant challenges, but with strategic planning and investment, there are opportunities for improving healthcare accessibility, quality, and affordability. The Purpose of this paper is to explore the Evolution of Healthcare, Growth of the Healthcare Sector, Contribution of Ayurveda, Charaka Samhita and Yoga to Healthcare, Drivers of Healthcare Sector, Challenges to Healthcare Sector and Prospect of Industry 4.0 and Healthcare Sector.